Epigenetic Reader Bromodomain Containing Protein 2 Facilitates Pathological Cardiac Hypertrophy via Regulating the Expression of Citrate Cycle Genes - Lin, Zhirong; Li, Zhenzhen; Guo, Zhen; Cao, Yanjun; Li, Jingyan; Liu, Peiqing; Li, Zhuoming (Frontiers in Pharmacology, 2022)
The bromodomain and extra-terminal domain proteins (BETs) family serve as epigenetic “readers”, which recognize the acetylated histones and recruit transcriptional regulator complexes to chromatin, eventually regulating gene transcription. Accumulating evidences demonstrate that pan BET inhibitors (BETi) confer protection against pathological cardiac hypertrophy, a precursor progress for developing heart failure. However, the roles of BET family members, except BRD4, remain unknown in pathological cardiac hypertrophy. The present study identified BRD2 as a novel regulator in cardiac hypertrophy, with a distinct mechanism from BRD4. BRD2 expression was elevated in cardiac hypertrophy induced by β-adrenergic agonist isoprenaline (ISO) in vivo and in vitro. Overexpression of BRD2 upregulated the expression of hypertrophic biomarkers and increased cell surface area, whereas BRD2 knockdown restrained ISO-induced cardiomyocyte hypertrophy. In vivo, rats received intramyocardial injection of adeno-associated virus (AAV) encoding siBRD2 significantly reversed ISO-induced pathological cardiac hypertrophy, cardiac fibrosis, and cardiac function dysregulation. The bioinformatic analysis of whole-genome sequence data demonstrated that a majority of metabolic genes, in particular those involved in TCA cycle, were under regulation by BRD2. Real-time PCR results confirmed that the expressions of TCA cycle genes were upregulated by BRD2, but was downregulated by BRD2 silencing in ISO-treated cardiomyocytes. Results of mitochondrial oxygen consumption rate (OCR) measurement and ATP production demonstrated that BRD2 augmented cardiac metabolism during cardiac hypertrophy. In conclusion, the present study revealed that BRD2 could facilitate cardiac hypertrophy through upregulating TCA cycle genes. Strategies targeting inhibition of BRD2 might suggest therapeutic potential for pathological cardiac hypertrophy and heart failure.